2000
DOI: 10.2981/wlb.2000.007
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale forest corridors to connect the taiga fauna to Fennoscandia

Abstract: Finland and Russian Karelia belong to the same biogeographical entity, lying on the same Precambrian bedrock. During the last half century there has been an enormous ‘natural experiment’, in which forestry in Finland has been very intensive, whereas in Karelia forestry has been negligent leaving large primaeval areas untouched. As a result, Russian forests have a much greater diversity of wildlife. In particular, rare species and species favouring old forests are more abundant in Karelia than in Finland. Typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…The future of some of the elementary components of the taiga in Fennoscandia depends on the condition of the taiga forests in Russia and on the connectivity of the Fennoscandian forest between Russia and Finland (Lindén et al 2000). Given the patterns of harvesting we monitored and the scenarios modeled, we suggest Conservation Ecology 7(2): 8. http://www.consecol.org/vol7/iss2/art8 that, in as little as 50 yr, near-natural forests in the study area will be found only in those areas that have been set aside for conservation.…”
Section: Conservation Implications: the Future Of The Vienansalo Forestsmentioning
confidence: 99%
See 3 more Smart Citations
“…The future of some of the elementary components of the taiga in Fennoscandia depends on the condition of the taiga forests in Russia and on the connectivity of the Fennoscandian forest between Russia and Finland (Lindén et al 2000). Given the patterns of harvesting we monitored and the scenarios modeled, we suggest Conservation Ecology 7(2): 8. http://www.consecol.org/vol7/iss2/art8 that, in as little as 50 yr, near-natural forests in the study area will be found only in those areas that have been set aside for conservation.…”
Section: Conservation Implications: the Future Of The Vienansalo Forestsmentioning
confidence: 99%
“…Many scientists have called for research in the Russian taiga, where extensive and relatively unmodified forest areas still exist (Syrjänen et al 1994, Uuttera et al 1996, Lindén et al 2000, Yaroshenko et al 2001. The study area is one of several large forest remnants in Fennoscandia along the Finnish border in Russian Karelia.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Studies dealing with population dynamics, factors affecting long-term changes in grouse populations, comparisons with adjacent areas' predator-prey interactions, and biodiversity aspects, as well as wildlife-habitat relationships and landscape ecology, have made fruitful use of the wildlife triangle data (Kurki et al 1998;Lindén et al 2000;Ranta et al 2006;Elmhagen et al 2010;Sirkiä et al 2010;Kojola et al 2014;among others).…”
Section: Wildlife Triangle Data For Multiple Usesmentioning
confidence: 99%